(untitled) - Barbour, Richmond (Cambridge, U.K., 2003)
This volume examines early Anglo-Indian relations through trade (with the establishment of the East India Company), tourism, and diplomacy and reveals important differences between traveller reports and the representations of London's press and stage. Richmond Barbour looks closely at exotic visions of "the East," as staged in the playhouses, at court, and on the streets of Shakespeare's London. He follows the efforts of the newly established East India Company, and the careers of England's first tourist and first ambassador in India, Thomas Coryate and Sir Thomas Roe.
Keywords: English drama,English drama,Theater,Exoticism in literature; Oriental influences,History and criticism,History; Early modern and Elizabethan, 1500-1600,17th century; England